Solidaritas Bagi Pasifik Selatan: Analisis Kebijakan Luar Negeri Selandia Baru dalam Menanggapi Isu Perubahan Iklim pada masa Pemerintahan Jacinda Ardern - Lyra Asaria Uthan; Mohamad Rosyidin; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
Since Jacinda Ardern's period as a prime minister in New Zealand, the country has contrasted climate change policy with the previous prime minister. Ardern's concern about climate change leads New Zealand to change the countries' diplomatic relations and add its foreign aid to the Pacific Islands countries. New Zealand's orientation and concern for the regional climate change crisis show a shift in Jacinda Ardern's leadership with her predecessor. This research aims to answer the research question: "Why does New Zealand actively participate in Pacific Island's climate change crisis during Jacinda Ardern Presidency?". This study aims to explain the role of Jacinda Ardern's ideas in shaping the climate change policy in the Pacific Islands. This research is explanative research using the desk research method. This study uses the framework of Ideas and Foreign policy by Judith Goldstein and Robert O. Keohane on answering which type of idea and how the policy-making mechanism that Ardern used.